2015
DOI: 10.3892/ol.2015.3700
|View full text |Cite
|
Sign up to set email alerts
|

Role of radiotherapy in the treatment of primary mediastinal large B-cell lymphoma

Abstract: Abstract. The role of radiotherapy (RT) in the treatment of primary mediastinal large B-cell lymphoma (PMLBCL) is unclear. In the present study, a retrospective analysis of 63 patients with PMLBCL treated with or without RT was performed to evaluate the role of RT. Clinical outcomes were calculated using the Kaplan-Meier method and were compared between patients who did and did not receive RT, using the log-rank test. A multivariate analysis was performed using Cox proportional hazards model. After chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Research from Korea demonstrated subsequent radiation did not produce a survival difference in terms of OS and PFS regardless of CHOP or RCHOP [4]. Wang et al did not conclude the positive significant role of subsequent IFRT after anthracyclinebased chemotherapy in PMBL patients [20]. More recent single institution data showed good OS rate of 79% by prospective study of dose-adjusted etoposide, doxorubicin, and cyclophosphamide with vincristine, prednisone, and rituximab (DA-EPOCH-R) without subsequent IFRT [21].…”
Section: Discussionmentioning
confidence: 99%
“…Research from Korea demonstrated subsequent radiation did not produce a survival difference in terms of OS and PFS regardless of CHOP or RCHOP [4]. Wang et al did not conclude the positive significant role of subsequent IFRT after anthracyclinebased chemotherapy in PMBL patients [20]. More recent single institution data showed good OS rate of 79% by prospective study of dose-adjusted etoposide, doxorubicin, and cyclophosphamide with vincristine, prednisone, and rituximab (DA-EPOCH-R) without subsequent IFRT [21].…”
Section: Discussionmentioning
confidence: 99%
“…3 More recently, radiation therapy, particularly stereotactic radiosurgery (SRS), has become an increasingly important treatment option for the initial management of patients with brain metastasis. 4 The efficacy of SRS, when used alone or combined with whole-brain radiation therapy, has been demonstrated in Phase III studies and has shown a 12-month local control rate of 70%-90%. [5][6][7][8] One of the most common complications after SRS for brain metastasis is radiation injury.…”
mentioning
confidence: 99%